Nicotine is a risk factor for dental caries: An in vivo study - Shiyu Liu; Tianmu Wu; Xuedong Zhou; Bo Zhang; Sibei Huo; Yutao Yang; Keke Zhang; Lei Cheng; Xin Xu; Mingyun Li (Elsevier, 2018)
Background/purpose: Streptococcus mutans is an important pathogen in the development of dental caries. Many studies have focused on the relationship between nicotine and S. mutans in vitro. The aim of this study was to investigate the effect of nicotine on the growth of S. mutans and its cariogenic potential in vivo. Materials and methods: Sixteen male Specific-pathogen-free Wistar rats were divided into 2 groups (nicotine-treated and nicotine-untreated group) and infected with S. mutans. The S. mutans suspension was treated with 1 mg/mL nicotine in the nicotine-treated group. The Keyes method was used to evaluate sulcal caries of rats, and dental plaque on molar teeth was observed by scanning electron microscopy (SEM). Results: Incidence of sulcal caries was higher in nicotine-treated group compared to nicotine-untreated group (42.7 ± 1.7 vs 37.3 ± 4.9, P = 0.009). Severity of caries increased with nicotine treatment. The slightly dentinal caries scores and moderate dentinal caries scores were higher in the presence of nicotine (P < 0.001). Increased number of S. mutans cells attached to dental surface was observed under SEM in the nicotine-treated group. Conclusion: Nicotine would promote the attachment of S. mutans to dental surface, and further increase the incidence and severity of dental caries. Therefore, nicotine might be a risk factor for smoking-induced caries. Keywords: Dental caries, Streptococcus mutans, Nicotine, Rats